The Effect of Rosemary (Rosmarinus officinalis L.) Antioxidant Extract on Palm Cooking Oil - Abdul Wakhid; Haslina; Hari Wibowo (Yayasan Meira Visi Persada, 2026)
Palm cooking oil is highly susceptible to quality deterioration due to lipid oxidation and degradation reactions during heating. This is characterized by an increased peroxide value and decreased iodine value. This study aimed to evaluate the potential of rosemary extract as a natural antioxidant to maintain palm cooking oil quality. The research used a Completely Randomized Design (CRD) with six concentrations of rosemary extract (0, 200, 400, 600, 800, and 1000 ppm) with three replications. Data were analyzed using ANOVA and a 5% DMRT. The results showed that adding rosemary extract significantly (P<0.05) decreased peroxide value (from 5.587 to 5.084 mEq/kg), increased iodine value (from 59.600 to 60.089), increased cloud point, and color value. Conversely, treatments had no significant effect (P>0.05) on moisture content and free fatty acids. The RSA-DPPH test also confirmed good free radical scavenging activity. In conclusion, the 1000 ppm concentration is the best treatment to effectively suppress the oxidation rate, indicating rosemary extract's high potential for application as a natural antioxidant in palm cooking oil.